THE INFLUENCE OF LEADERSHIP ON EMPLOYEE WORK DISCIPLINE AT THE GORONTALO CITY EDUCATION OFFICE - Bayahu, Amelia Putri Utami; Tohopi, Rustam; Tantu, Romy (Public Policy Journal, 2024)
This study aims to determine the influence of leadership on employee work discipline at the Gorontalo City Education Office. The approach in this study is quantitative with ex-post facto methods. Data collection in this study was carried out by questionnaire. The number of samples was 93 people obtained by the saturated sampling process. Data analysis in this study is a simple linear regression inferential quantitative analysis. The results showed that leadership had a positive and significant effect on the work discipline of employees at the Gorontalo City Education Office with a coefficient of determination of 56.50%. The influence of other variables on employee work discipline amounted to 43.50%, namely goals and abilities, leadership examples, remuneration, justice, inherent supervision (waskat), punitive sanctions, firmness, and humanitarian relations. When the leader implements the ideal leadership function, it will have an impact on the good discipline of employees at the Gorontalo City Education Office, both in terms of attitude discipline and time discipline.